INVESTIGATING LINGUISTICS FACTORS AFFECTING ISLAMIC BOARDING SCHOOL STUDENT’S ENGLISH SPEAKING PERFORMANCE - Taufik Afdal; Joko Iswanto (Universitas Negeri Islam Sumatera Utara, 2022)
This paper seeks to investigate linguistics factors affecting students in speaking English at Khadimul Ummah Islamic Boarding School, Bintan, Kepri. A total of ten students comprising 4 female students and 6 male students of senior high school participated in this research. Open-ended interviews were used to collect the data. The data in the forms of utterances were recorded. They were further analyzed and classified according to linguistic factors. The errors detected were further elaborated. Based on the data analysis, it was found that the majority of students commit errors of vocabulary followed by omission, addition and pronunciation. Thus, the most dominant linguistic factor in this case is vocabulary. It is suggested that the tutors of the English speaking program should provide feedbacks on students’ errors in order to get students used to good grammar usage, proper vocabulary and pronunciation. In addition, introducing collocations to students will help them speak naturally and fluently. Keywords: Speaking Problems, Islamic Boarding School, Speaking Anxiety